Role of viability of probiotic strains in their persistence in the gut and in mucosal immune stimulation - Maldonado Galdeano, María Carolina (2004)
Aims: To determine how probiotic bacteria contact with intestinal epithelial and immune cells and the conditions to induce a good mucosal immune stimulation. Methods and Results: Lactobacillus casei was studied by transmission electron microscopy (TEM) to determine its interaction with the gut. We compared the influence of viable and nonviable lactic acid bacteria on the intestinal mucosal immune system (IMIS) and their persistence in the gut of mice. TEM showed whole Lact. casei adhered to the villi; the bacterial antigen was found in the cytoplasm of the enterocytes. Viable bacteria stimulated the IMIS to a greater extent than nonviable bacteria with the exception of Lact. delbrueckii subsp. bulgaricus. For all the strains assayed at 72 h no antigenic particles were found in the intestine. Conclusion: Antigenic particles but not the whole bacteria can enter to epithelial cells and contact with the immune cells. Bacterial viability is a condition for a better stimulation of the IMIS. Significance and Impact of the Study: We demonstrated that only antigenic particle interact with the immune cells and their fast clearance from the gut agrees with those described for the particulate antigens. The regular consumption of probiotics should not adversely affect the host.